2021
DOI: 10.1111/jocd.14257
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind, placebo‐controlled split‐face trial of the efficacy of tranexamic acid by drug delivery through microneedling in the treatment of melasma

Abstract: Melasma is a skin pigmentation disorder characterized by irregular brownish macules, symmetrically distributed in photoexposed areas, most commonly on the face. It is more common in women, with a higher phototype (III-IV) and in fertile age. Due to the high prevalence, the predominantly facial involvement, and the high index of therapeutic recurrence, melasma has an important impact on quality of life, being a frequent cause of dermatological consultations. 1,2 The exact pathophysiology of melasma is not yet k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Results showed improvement in both sides with a better, but not significant, improvement in the TXA side using the hemi-MASI scale. 28 Comparatively, another study performed microneedling to the entire face with the application of 10% TXA to one side and distilled water on the other side in 40 patients (dermaroller, 1 mm depth). This was done four times every 2 weeks with a final visit at week 8.…”
Section: Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Results showed improvement in both sides with a better, but not significant, improvement in the TXA side using the hemi-MASI scale. 28 Comparatively, another study performed microneedling to the entire face with the application of 10% TXA to one side and distilled water on the other side in 40 patients (dermaroller, 1 mm depth). This was done four times every 2 weeks with a final visit at week 8.…”
Section: Evidencementioning
confidence: 99%
“…A double‐blind, split‐faced RCT compared microneedling topical 5% TXA to microneedling with a placebo in 3 monthly sessions for 20 patients in addition to a topical treatment regimen of 0.5% retinoic acid, 4% hydroquinone, and 0.01% fluocinolone acetonide (polyethylene roll, 1.5 mm needle length). Results showed improvement in both sides with a better, but not significant, improvement in the TXA side using the hemi‐MASI scale 28 . Comparatively, another study performed microneedling to the entire face with the application of 10% TXA to one side and distilled water on the other side in 40 patients (dermaroller, 1 mm depth).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of microneedling is to improve drug delivery, which has shown promising results with TXA in previous studies. 13 This has been challenged by Kuster et al, 19 who demonstrated that TXA through microneedling did not bring about any additional benefit to the treatment of melasma; nonetheless, they first performed microneedling and then applied TXA. Contrarily, Ebrahim et al 20 showed that microneedling of TXA was as safe and effective as its intradermal injection with higher patient satisfaction with microneedling, which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Photoelectric therapy like intense pulsed light and various lasers have also been used 14,16–19 . However, the treatment approach of using a single method has certain limitations; thus, combination therapy is more likely to be developed and applied in the clinical treatment of melasma 5,20 …”
Section: Discussionmentioning
confidence: 99%
“…At present, there are various treatments for melasma, including photoelectric and drug therapies 4 . Tranexamic acid (TA) has been used in the treatment of melasma and has shown good therapeutic effects; it is given orally or via intradermal injection 5–7 . Photoelectric therapy is also one of the main treatment methods for melasma.…”
Section: Introductionmentioning
confidence: 99%